Nutritional and performance viability of cactus Opuntia-based diets with different concentrate levels for Girolando lactating dairy cows - Jonas Gomes Inácio; Maria Gabriela da Conceição; Djalma Cordeiro dos Santos; Júlio César Vieira de Oliveira; Juana Catarina Cariri Chagas; Gláucia Sabrine de Oliveira Moraes; Evannielly Thuanny dos Santos Silva; Marcelo de Andrade Ferreira (Asian-Australasian Journal of Animal Sciences, 2020)
Objective The aim of this research was to evaluate the effect of different concentrate levels in diets based on cactus Opuntia Stricta (Haw.) Haw cladodes on the performance of lactating Girolando cows. Methods The experiment involved 10 Girolando multiparous dairy cows at 512.6 kg of body weight (BW) and producing 13.2 kg milk/d, allocated into two 5×5 Latin squares. The experimental treatments consisted of control diet composed by cactus Nopalea cochenillifera. Salm-Dyck. cladodes (Nopalea), forage sorghum silage and concentrate at 20% on dry matter (DM) basis, and four concentrate levels diets (20%, 24%, 28%, and 32%) plus cactus Opuntia stricta (Haw.) Haw. cladodes (Opuntia) and forage sorghum silage. Results Regarding cows fed control diet, the nutrients intake were greater than for cows fed with cactus Opuntia and concentrate. Regarding concentrate levels, intakes of DM, organic matter (OM), crude protein (CP), non-fiber carbohydrates (NFC), and total digestible nutrients of cows increased linearly. Organic matter, CP, and NDF digestibilities were similar in between to control diet and cactus Opuntia-based diets. The digestibility of NFC increased linearly when the concentrate was inserted. The N balance was the same for control diet and cactus Opuntia-based diets, irrespective the concentrate levels. Conclusion For cows producing 14 kg/d with 3.5% of fat, it is recommended 32% of concentrate to be included in cactus Opuntia-based diets, and the increase in concentrate level promotes a linear increase in milk yield.